2021
DOI: 10.4103/jpbs.jpbs_561_20
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Based Rapid Tissue Processing Technique: A Novel Aid in Histopathologic Laboratory

Abstract: Introduction: Conventional tissue processing takes a lot of time, but microwave processing method though rapid, its quality of tissue texture and staining properties is still questionable. Therefore, we conducted this study to find out the reliability of histological sections in the microwave method. Aim and Objectives: The aim is to assess whether microwave tissue processing, which is a rapid technique, is comparable to conventional tissue processing in terms of qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the last decades, several studies have reported comparable results on the diagnostic ability of conventional and microwave tissue processing [45,46]. Being a labor-intensive method, microwaves have been primarily applied to the processing of small biopsies taken from patients for whom the diagnosis is crucial to guide life-saving treatments.…”
Section: Fast Sample Management Protocols and Stainsmentioning
confidence: 99%
“…In the last decades, several studies have reported comparable results on the diagnostic ability of conventional and microwave tissue processing [45,46]. Being a labor-intensive method, microwaves have been primarily applied to the processing of small biopsies taken from patients for whom the diagnosis is crucial to guide life-saving treatments.…”
Section: Fast Sample Management Protocols and Stainsmentioning
confidence: 99%